1994
DOI: 10.1002/j.1460-2075.1994.tb06243.x
|View full text |Cite
|
Sign up to set email alerts
|

An iron-sulfur center essential for transcriptional activation by the redox-sensing SoxR protein.

Abstract: The soxRS oxidative stress regulon of Escherichia coli is triggered by superoxide (O2.‐) generating agents or by nitric oxide through two consecutive steps of gene activation. SoxR protein has been proposed as the redox sensing gene activator that triggers this cascade of gene expression. We have now characterized two forms of SoxR: Fe‐SoxR contained non‐heme iron (up to 1.6 atoms per monomer); apo‐SoxR was devoid of Fe or other metals. The spectroscopic properties of Fe‐SoxR indicated that it contains a redox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
285
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(292 citation statements)
references
References 52 publications
7
285
0
Order By: Relevance
“…The [2Fe-2S] centers in purified WT SoxR protein produce a visible absorption spectrum with four maxima at 332, 414, 462, and 548 nm (35,36). Absorption spectra of the purified mutant proteins (data not shown) corroborated the results obtained from in vivo EPR spectroscopy (Fig.…”
Section: Functional Analysis Of Soxr Mutant Proteinssupporting
confidence: 76%
“…The [2Fe-2S] centers in purified WT SoxR protein produce a visible absorption spectrum with four maxima at 332, 414, 462, and 548 nm (35,36). Absorption spectra of the purified mutant proteins (data not shown) corroborated the results obtained from in vivo EPR spectroscopy (Fig.…”
Section: Functional Analysis Of Soxr Mutant Proteinssupporting
confidence: 76%
“…The first evidence in this regard was that the SoxR apoprotein was transcriptionally inactive in vitro (9). Subsequently, it was found that whereas SoxR ox is active in vitro (6,10), it can be inactivated by anaerobic reduction with dithionite and then rapidly restored by autooxidation (3).…”
Section: Discussionmentioning
confidence: 99%
“…This disassembly may be facilitated in vitro by thiols (6,7). The apoprotein is inactive although it can still bind to DNA (9), whereas the holoprotein can activate the transcription of soxS (9,10). This model was probably promoted because of early failures to verify the alternative model (6).…”
mentioning
confidence: 99%
“…SoxR appears to be a sensor of superoxides and resembles the MerR family of gene regulators (1,38). Recently, an Fe-SoxR protein which activates the transcription of soxS in vitro has been identified (17). The considerable amino acid sequence homologies predicted for the MarA and SoxS proteins from their nucleotide sequences suggest that they may have functions similar to those of AraC-type transcriptional activators (1,6,10).…”
mentioning
confidence: 99%